Combining Mathematical Models With Experimentation to Drive Novel Mechanistic Insights Into Macrophage Function - Jansen, Joanneke E.; Gaffney, Eamonn A.; Wagg, Jonathan; Coles, Mark C. (Frontiers in Immunology, 2019)
This perspective outlines an approach to improve mechanistic understanding of macrophages in inflammation and tissue homeostasis, with a focus on human inflammatory bowel disease (IBD). The proposed approach integrates wet-lab and in-silico experimentation, driven by mechanistic mathematical models of relevant biological processes. Although wet-lab experimentation with genetically modified mouse models and primary human cells and tissues have provided important insights, the role of macrophages in human IBD remains poorly understood. This is despite comprehensive experimental assessments based on transcriptomics (population and single cell), proteomics and immunohistochemistry. Key open questions include: (1) To what degree hyperinflammatory processes (gain of cytokine production) and immunodeficiency (loss of bacterial killing) intersect to drive IBD pathophysiology? and (2) What are the roles of macrophage heterogeneity in IBD onset and progression? Mathematical modelling offers a synergistic approach that can be used to address these questions. Mechanistic models are useful for informing wet-lab experimental designs and provide a knowledge constrained framework for quantitative analysis and interpretation of resulting experimental data. The majority of published mathematical models of macrophage function are based either on animal models, or immortalised human cell lines. These experimental models do not recapitulate all relevant features of human gastrointestinal pathophysiology, therefore, are limited in the extent to which they can fully inform understanding of human IBD. Thus, we envision a future where mechanistic mathematical models are based on richer human datasets, including biopsy tissues taken from IBD patients, and other high-throughput clinical data derived from experimental medicine studies and/or clinical trials on IBD patients.